Euro-Mediterranean Association: from the Barcelona process to the Union for the Mediterranean - Natalya Anikeeva (Ибероамериканские тетради, 2018)
The Mediterranean has been the priority direction in the politics of Spain in the post-Franco era. When Spain entered the EEC in 1986 and participated between 1990 and 2000 in the Barcelona Process and the founding of the Union for the Mediterranean, the Mediterranean accent of its policy became even clearer. The Spain of today’s stage shares, in broad strokes, the EU’s approaches to politics in the Mediterranean region.      The Spanish School of Mediterranean Studies is represented by a series of fundamental works from the centers of the International Research Institute of Barcelona, the Autonomous University of Madrid and other specialized institutions. In our study, the publications of famous public figures from Spain that came to light in the Spanish magazine “Política Exterior” are particularly important.      The UPM was founded on July 13, 2008, during the Paris Summit for the Mediterranean, which was attended by representatives of 43 nations. Its implementation, however, took time to complete. The obstacles to the operation of the project were due to a series of causes. They were provoked, first of all, by the disparity between the EU members and the Mediterranean countries, as well as by the consequences of the Arab Spring, by the challenges of the Arab-Israeli settlement, and by the EU’s policy regarding some states in the region, in particular, to Syria.Cooperation and development in the Mediterranean are the objective of the Union for the Mediterranean (UfM), an association that promotes peace and prosperity for an area with 750 million inhabitants.